Sleep Duration and Incidence of Type 2 Diabetes: The Multiethnic Cohort - Maskarinec, Gertraud (Sleep Health, 2017)
OBJECTIVES: As an emerging risk factor for the rising incidence of type 2 diabetes, we examined sleep duration in relation to type 2 diabetes and several biomarkers. DESIGN: Prospective cohort recruited 1993–1996. SETTING: The Multiethnic Cohort in Hawaii and California. PARTICIPANTS: A cohort of 151,691 white, African American, Japanese American, Native Hawaiian, and Latino participants; 9,695 cohort members had biomarker measurements. MEASUREMENTS: Sleep duration was self-reported at cohort entry. Diabetes status was obtained from three questionnaires and confirmed by three administrative data sources. Biomarkers were measured by standard assays 9.6±2.1 years after cohort entry. We estimated diabetes risk as a time varying outcome using Cox regression adjusted for body mass index assessed at three time points and other known confounders and computed adjusted means of biomarkers by sleep hours. RESULTS: During 7.9±3.5 years of follow-up, 8,487 new diabetes cases were diagnosed. Long sleep duration (≥9 hours), as compared to 7–8 hours, was significantly associated with higher incidence (HR, 1.12; 95%CI 1.04, 1.21), but the 4% elevated incidence for short sleep duration (≤6 hours) did not reach significance (95%CI 0.99, 1.09). After stratification, the associations appeared stronger in Japanese American than other ethnic groups and in participants without comorbidity. Hours of sleep were positively associated with CRP and triglycerides and inversely related to HDL-cholesterol and adiponectin but not with leptin levels and HOMA-IR. CONCLUSION: In this multiethnic population, the 12% higher diabetes risk for long sleep hours may be mediated through inflammation, a poor lipid profile, and lower adiponectin levels.